Herbaceous plant strategies in disturbed habitats - Schippers, Peter; Van Groenendael, Jan M.; Vleeshouwers, Leo M.; Hunt, Roderick (Oikos, 2001)
A systematic theoretical evaluation has been made of three important plant life history traits: adult longevity, seed longevity and seed mass, where seed mass is interpreted as being indicative of dispersal distance and seedling vigour. This model study examined the role of these three traits in relation to environmental disturbance. We chose temperate grasslands, widespread in north Western Europe and northern and eastern America, as our reference system for our simulations. Eight plant strategies were defined by allowing two levels in each of the three and combining them in all eight possible ways. A simple, spatially explicit model was developed to simulate competition among individuals with these eight trait combinations at different levels of disturbance. Simulation results were compared with the actual occurrence over a disturbance gradient of species with similar plant trait combinations in a large database from the Sheffield area (UK). This showed that with increasing disturbance level, non-dormant perennials, dormant perennials, non-dormant annuals and dormant annuals, respectively, became dominant but only if small-seeded, indicating the relative viability of these particular strategies with respect to disturbance. A new prediction from the model was that stable coexistence occurs between plant strategies with dormant and with non-dormant seeds over a range of levels of disturbance. Plant strategies with large seeds were inferior to small-seeded ones if competitive ability of seedlings is proportional to seed weight. This difference was highest at low seed densities and low germination probabilities, indicating that large-seeded species secure no advantage from being dormant (i.e. having a low germination probability). Finally, the results indicated that dormancy is superior to dispersal as a method of coping with disturbance.